Disaster and development - Collins, Andrew E. (London Routledge, 2009)
This engaging and accessible text illuminates the complexity of the relationship between disaster and development. It opens with an assessment of the scope of contemporary disaster and development studies, highlighting the rationale for looking at the two issues as part of the same topic. The second and third chapters detail development perspectives of disaster, and the influence of disaster on development. The fourth chapter exemplifies how human health is both a cause and consequence of disaster and development and the following chapter illustrates some of the learning and planning processes in disaster and development oriented practice. Early warning, risk management, mitigation, response and recovery actions provide the focus for the fifth and sixth chapters. The final chapter indicates some of the likely future contribution and challenges of combined disaster and development approaches. With an emphasis on putting people at the centre of disaster and development, the book avoids confronting readers with ?no hope? representations, instead highlighting disaster reduction opportunities.
Includes bibliographical references (p. [263]-277) and index.
Keywords: Economic development